Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5802/afst.1251
|View full text |Cite
|
Sign up to set email alerts
|

Invariant Spin Structures on Riemann Surfaces

Abstract: We investigate the action of the automorphism group of a closed Riemann surface on its set of theta characteristics (or spin structures). We give criteria for when an automorphism fixes all spin structures, or when it fixes just one. The case of hyperelliptic curves and of the Klein quartic are discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The question which automorphisms σ C of C lift to a spin curve (X, L, b) with stable model C is difficult, even in the case of a smooth curve C. By Atiyah's result for every automorphism σ C ∈ Aut C of a smooth curve C there exists at least one theta characteristic L on C such that σ C lifts to the spin curve (C, L, b). Moreover, S. Kallel and D. Sjerve show in [KS06] that an automorphism σ C ∈ Aut C, where C is smooth, lifts to every theta characteristic L on C if and only if C is hyperelliptic and σ C is the hyperelliptic involution. Therefore, for every automorphism σ C which is not a hyerelliptic involution there exists at least one theta characteristic to which σ C lifts and at least one to which it does not lift.…”
mentioning
confidence: 99%
“…The question which automorphisms σ C of C lift to a spin curve (X, L, b) with stable model C is difficult, even in the case of a smooth curve C. By Atiyah's result for every automorphism σ C ∈ Aut C of a smooth curve C there exists at least one theta characteristic L on C such that σ C lifts to the spin curve (C, L, b). Moreover, S. Kallel and D. Sjerve show in [KS06] that an automorphism σ C ∈ Aut C, where C is smooth, lifts to every theta characteristic L on C if and only if C is hyperelliptic and σ C is the hyperelliptic involution. Therefore, for every automorphism σ C which is not a hyerelliptic involution there exists at least one theta characteristic to which σ C lifts and at least one to which it does not lift.…”
mentioning
confidence: 99%
“…This theorem was also proved using different methods in [9]. Yet, We prove it here using our methods as in the proof of Theorem 20.…”
Section: Invariant M-spin Structures On a Hyperelliptic Surface Undermentioning
confidence: 81%
“…In other words, f fixes 2 2g+2 n −2 2-spin structures. This theorem was proved using different methods in [9]. We prove it here using similar methods to the ones we used to prove Theorems 16 and 18.…”
Section: Invariant M-spin Structures On a Hyperelliptic Surface Undermentioning
confidence: 98%
See 1 more Smart Citation
“…Assume that X admits nontrivial automorphisms; fix a nontrivial automorphism σ of X . In [3] it was shown that if σ fixes all the theta characteristics of X pointwise, then X is hyperelliptic and σ is the unique hyperelliptic involution of X (this was also proved in [5]). Our aim here is to address a similar question for curves defined over the field of real numbers.…”
Section: Introductionmentioning
confidence: 80%